Case Report: Kommerell's diverticulum and left aberrant subclavian artery stenosis hybrid treatment with branched aortic stent-graft - Rodríguez-Pérez, Álvaro; Tello-Diaz, Cristina; Vergara-Budding, A. Carolina; Fernández-Vinzenzi, Constanza; Hakim Moustafa, Abdel; Acebes Pinilla, Cesar; Ginel-Iglesias, Antonino; Barros-Membrilla, Antonio J.; Dilme-Muñoz, Jaime Felix (Frontiers in Cardiovascular Medicine, 2023)
Kommerell's diverticulum in association with left or right aberrant subclavian arteries is a rare finding and is challenging to treat. Contemporary surgical and endovascular techniques provide a broad arsenal of possible treatments. Imaging techniques and modeling technology allow a more personalized strategy for each patient. In this case, we present a symptomatic patient with a Kommerell's diverticulum and a left aberrant subclavian artery complicated by proximal stenosis and poststenotic aneurysm. A hybrid technique using a single-branched thoracic stent-graft (Castor, MicroPort Medical, Shanghai, China) in combination with a surgical left subclavian-carotid bypass and endovascular occlusion of the poststenotic aneurysm using a vascular plug device (Amplatzer Vascular Plug, Abbott, Chicago, United States) was performed. This approach was planned and facilitated by the use of a 3D model. Alternative treatment options and the strengths of this approach are briefly reviewed and discussed.